Water budgeting in conservation agriculture‑based sub‑surface drip irrigation in maize-wheat rotation using HYDRUS‑2D model for South Asia - CGIAR Research Program on Wheat (2021)
Multi-year systematic research showed the complementarity of conservation agriculture and sub-surface drip irrigation, assessed through field experimentation and simulation modelling. Considering the future consequences of rapidly depleting groundwater, Governments (India, Punjab, Haryana) initiated a new policy to save water in agriculture. ‘Science driven Policy’ is needed for effective execution.